ANALISIS KOMPARATIF KINEMATIKA GERAK MENENDANG PADA ANAK USIA DINI DAN USIA SEKOLAH DASAR: STUDI OBSERVASIONAL BERBASIS BELAJAR GERAK - Pandu Dinata Agustian; Meli Agustina Purba; Nailatus Sefia; Rahma Dewi; Siti Rahima Gultom (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The developmental trajectory of kicking movements in children represents a complex phenomenon governed by progressive kinematic adaptation and neuromotor regulation. This study comparatively analyzed kicking kinematics between early childhood (ages 4–6) and primary school-age children (ages 7–12) using an observational approach grounded in motor learning theory. Field observations concentrated on four primary dimensions: inter-segmental coordination, dynamic stability, kicking power, and motor decision-making latency. Findings revealed that early childhood participants exhibited gross coordination characteristics—marked by substantial center-of-mass (COM) instability, kinetic chain asynchrony, and considerable postural oscillation during the approach phase. Primary school-age children, by contrast, demonstrated more mature movement consolidation evidenced by greater kicking velocity and consistency; nevertheless, residual motor decision-making latency (150–250 ms) was identified as a limiting factor for attacking efficiency. The discussion integrates Gallahue's motor development phases and Schmidt's Schema Theory, supported by recent empirical evidence. The study concludes that developmentally differentiated training programmes are essential for optimizing the kicking skill trajectory in a structured and age-appropriate manner.